Caregiver Emotions When Choosing A Living Environment for A Person with Dementia: A Qualitative Study on Social Workers' Perspectives. Issue 1 (2nd January 2022) - Gaudet, K.; Couture, M.; Ducharme, F.; Saïas, T.
ABSTRACT: Social workers often address the emotional needs of family caregivers, which are particularly salient during the decision-making process regarding the choice of a living environment for a relative with dementia. In most home care settings, an assessment of caregivers' needs is not part of routine practices. This study aims to describe the intervention strategies adopted by social workers in relation to caregivers' emotions during their decision-making process. A qualitative research design was adopted. Seven social workers were recruited from three health and community service facilities in Montreal, Canada. One group and three individual semi-structured interviews were conducted. Data was analyzed using Miles, Huberman and Saldaña's method (2013). Seven intervention strategies were identified: investigating emotions, acknowledging emotions, encouraging caregivers to carry on their role, focusing on the rational aspects of the decision, mitigating prejudices against nursing homes, mediating family dynamics and acting upon families' needs . Some of these strategies are aimed at social workers meeting the demands of their jobs whilst others are centered around soothing caregiver emotions. These results can inform support services and future interventions by grounding them in the realities of service providers.